The graphene surface force balance - van Engers, C (2018)
The importance of capturing, storing and converting energy, exemplified through the desire for independence from fossil fuels and everyday use of portable electronic devices, has magnified interest in understanding processes at the interface between solids and electrolytes. This thesis explores different experimental approaches towards measuring surface forces across electrolytes confined between polarizable surfaces in the Surface Force Balance (SFB). The main findings of the thesis concern the fabrication and implementation of graphene SFB (gSFB) lenses, which use graphene as transparent conductor for surface force measurements at the solid/electrolyte interface. Such lenses consist of hemi-cylindrical quartz discs, with a reflective coating and a graphene layer supported by epoxy. The suitability of different graphenes produced using Chemical Vapor Deposition was investigated, concomitant with the development of a fabrication method for such lenses, including the fabrication of uniform epoxy layers and the template stripping of epoxy supported graphene from mica templates. It was found that the smoothness of the graphene surfaces on the lenses was limited and factors contributing to this limitation are discussed. Analysis techniques were developed for the efficient determination of the contact distance without performing a contact calibration and determination of the radius of curvature using secondary Fringes of Equal Chromatic Order. Using these procedures, the surface and interfacial energy of graphene in dry nitrogen and liquids was determined by applying JKR-theory to adhesion force measurements. The presented fabrication and analysis techniques are not limited to gSFB and may be applied to different SFB setups. As such, the exciting prospect of using the newly developed methods in an alternative 3-mirror setup is discussed as well. The work presented in this thesis contributes two novel techniques for the measurement of surface forces across electrolytes with control of the surface electrical potential and will allow for exciting new experiments.